(untitled) (World Bulletin of Social Sciences, 2024)
This article is about the book "Folk Puppet Theater" by Academician Muhsin Kadirov, an Uzbek theater scholar. The article contains opinions about the content of the book and its importance in today’s science of art. It is acknowledged that scientist left a priceless legacy by studying the ancient types of performing arts of the Uzbek people.